2008
DOI: 10.1038/sj.bjc.6604453
|View full text |Cite
|
Sign up to set email alerts
|

Rapid progression of prostate cancer in men with a BRCA2 mutation

Abstract: Men with BRCA2 mutations have been found to be at increased risk of developing prostate cancer. There is a recent report that BRCA2 carriers with prostate cancer have poorer survival than noncarrier prostate cancer patients. In this study, we compared survival of men with a BRCA2 mutation and prostate cancer with that of men with a BRCA1 mutation and prostate cancer. We obtained the age at diagnosis, age at death or current age from 182 men with prostate cancer from families with a BRCA2 mutation and from 119 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
103
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(110 citation statements)
references
References 10 publications
2
103
1
4
Order By: Relevance
“…This may help delineate PSAV among men diagnosed with PrCa with low PSA values (Carter et al, 1992; Kitagawa et al, 2014). A strength of this study is the unique patient cohort of men with a genetic predisposition to PrCa, in particular BRCA2 carriers who are predisposed to aggressive PrCas (Mitra et al, 2008;Narod et al, 2008;Castro et al, 2013;Castro et al, 2015). Within the group of BRCA2 carriers, PSAV proved predictive of any grade cancer, however, given the low number of cancers diagnosed overall it was not possible to assess whether PSAV was associated with high grade cancer and BRCA2 status.…”
Section: Discussionmentioning
confidence: 99%
“…This may help delineate PSAV among men diagnosed with PrCa with low PSA values (Carter et al, 1992; Kitagawa et al, 2014). A strength of this study is the unique patient cohort of men with a genetic predisposition to PrCa, in particular BRCA2 carriers who are predisposed to aggressive PrCas (Mitra et al, 2008;Narod et al, 2008;Castro et al, 2013;Castro et al, 2015). Within the group of BRCA2 carriers, PSAV proved predictive of any grade cancer, however, given the low number of cancers diagnosed overall it was not possible to assess whether PSAV was associated with high grade cancer and BRCA2 status.…”
Section: Discussionmentioning
confidence: 99%
“…Narod et al 90 reported a series of 67 BRCA2 and 37 BRCA1 mutation carriers or obligate carriers of different BRCA mutations. The study analysed the prognosis of BRCA1 vs. BRCA2 mutation carriers and did not include a BRCA wild-type group for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] BRCA2 is a tumour suppressor protein involved in the repair of DNA double-strand breaks via homologous recombination (HR). Tumour tissues derived from BRCA2 mutation carriers (e.g., male or female breast cancers, ovarian cancer and prostate cancer being the most common) may respond differently to radiotherapy (RT) and chemotherapy when compared to tumours with normal BRCA2 and HR protein function.…”
Section: Introductionmentioning
confidence: 99%